High incidence of Mycobacterium avium subspecies hominissuis infection in a zoo population of bongo antelopes (Tragelaphus eurycerus) - Moravkova, Monika; Mrlik, Vojtech; Parmova, Ilona; Kriz, Petr; Pavlik, Ivo (Journal of veterinary diagnostic investigation, 2013)
Mycobacterium avium subsp. hominissuis (Mah) infection was diagnosed in 5 captive bongo antelopes (Tragelaphus eurycerus) originating from a collection in a zoological garden. The animals suffered from emaciation. Postmortem examination revealed nodular lesions in the lungs of all 5 examined animals. Acid-fast bacilli were observed in the lungs of 4 animals. Culture and polymerase chain reaction identification based on IS901 negativity and IS1245 positivity confirmed Mah infection in the lungs of all 5 antelopes. In 3 animals, Mah was also isolated from other organs (liver, spleen, and kidney). Molecular analysis of these isolates using IS1245 restriction fragment length polymorphism and/or mycobacterial interspersed repetitive units-variable number tandem repeat revealed that the studied antelopes were infected by 1 identical genotype. Furthermore, in 2 antelopes, other genotypes were also detected. This shows the possibility of either genetic modifications occurring during infection or polyclonal infection. Culture examination of environmental samples from the enclosures holding the bongos revealed Mah in mulch bark, peat, and soil. Genotyping of these environmental isolates determined several genotypes with 1 dominant genotype that was identical to the dominant genotype detected in antelopes.
Keywords: polymerázová řetězová reakce; tuberkulóza; Tuberculosis; DNA bakterií; Incidence; Feces; Polymerase Chain Reaction; Genotype; zvířata v ZOO; DNA, Bacterial; feces; Animals, Zoo; půdní mikrobiologie; DNA Transposable Elements; Soil Microbiology; zvířata; antilopy; Mycobacterium avium; Fatal Outcome; Animals; genotyp; Antelopes; incidence; transpozibilní elementy DNA; Lung Diseases; fatální výsledek; plicní nemoci